Primary or metastatic branchial cleft carcinoma?: a case report - Ma, Yang; Liu, Hangyu; Yang, Lijing; Tang, Shijie; Shi, Lungang (Frontiers in Surgery, 2023)
The brachial cleft carcinoma is an extremely rare head and neck facial malignancy, and there is some disagreement about its differential diagnosis. In this paper, we report a 63-year-old male patient who had a mass on the left side of the neck and diagnosed as the brachial cleft carcinoma by intraoperative biopsy pathology. However, this patient was diagnosed with the carcinoma of the left soft palate more than 20 days after surgery and esophageal cancer 2 years later, and was treated accordingly. Therefore, it is hard to confirm whether the branchial cleft carcinoma is primary or metastatic. In fact, the diagnostic criteria for primary squamous cell carcinoma of branchial cleft cysts are very rigorous. Confirmation of the diagnosis is based on pathological examination of the branchial cleft cyst epithelium lined with squamous cells, meanwhile, a thorough examination should also be performed to exclude the presence of other primary cancers.